2020
DOI: 10.1101/2020.05.09.081547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis and annotation of genome-wide DNA methylation patterns in two nonhuman primate species using the Infinium Human Methylation 450K and EPIC BeadChips

Abstract: The Infinium Human Methylation450 and Methylation EPIC BeadChips are useful tools for the study of the methylation state of hundreds of thousands of CpG across the human genome at affordable cost. However, in a wide range of experimental settings in particular for studies in infectious or brain-related diseases, human samples cannot be easily obtained. Hence, due to their close developmental, immunological and neurological proximity with humans, nonhuman primates are used in many research fields of human disea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…One potential limitation of this study is that human microarrays were used to measure DNA methylation on non-human primate genomes. However, alignment and stringent quality control of the included probes to the AGM and MAC genomes revealed that still 162,053 and 158,970 probes could be confidently used covering 16,295 and 16,611 genes, respectively [38]. Of those, 157,164 and 154,108 probes were detected with high confidence in the current study.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…One potential limitation of this study is that human microarrays were used to measure DNA methylation on non-human primate genomes. However, alignment and stringent quality control of the included probes to the AGM and MAC genomes revealed that still 162,053 and 158,970 probes could be confidently used covering 16,295 and 16,611 genes, respectively [38]. Of those, 157,164 and 154,108 probes were detected with high confidence in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…Using the Infinium HumanMethylation450K Bead-Chip (Illumina) by restricting the analysis to a subset of probes that target CpGs at a unique location on the MAC and AGM genomes, we were able to study methylation at 157,164 and 154,108 CpG sites for AGM and MAC, respectively [38]. As expected, genome-wide methylation pattern showed a typical bimodal distribution (Additional file 1: Figure 4A) and a strong correlation was observed when all probes were compared between MAC and AGM (Additional file 1: Figure 4B).…”
Section: Effect Of Siv Infection On Dna Methylation Patterns In Cd4 +mentioning
confidence: 99%
See 2 more Smart Citations
“…A broad body of evidence suggests that environmental and experiential factors can trigger cascades of epigenetic modification that in turn mediate downstream molecular and behavioral phenotypes. In this study, we focused on DNA methylation in rhesus macaque and human blood samples using the flexibility of Illumina DNA methylation arrays as a translational platform to investigate DNA methylation in both human and non-human primate species [42][43][44][45] . In fact, we were able to identify Moreover, a DMR in PM20D1 similar to our results was recently identified in human blood samples in a longitudinal study of post-traumatic stress disorder 48 , and CAMK2A is one of the most well-understood genes mediating synaptic plasticity underlying fear learning in a variety of paradigms 49 .…”
Section: Discussionmentioning
confidence: 99%